2021
DOI: 10.3390/ijerph18136941
|View full text |Cite
|
Sign up to set email alerts
|

How Task Constraints Influence the Gaze and Motor Behaviours of Elite-Level Gymnasts

Abstract: Perception-action coupling is fundamental to effective motor behaviour in complex sports such as gymnastics. We examined the gaze and motor behaviours of 10 international level gymnasts when performing two skills on the mini-trampoline that matched the performance demands of elite competition. The presence and absence of a vaulting table in each skill served as a task-constraint factor, while we compared super-elite and elite groups. We measured visual search behaviours and kinematic variables during the appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…During this phase gymnasts start to approach an optimal body position to contact the mini trampoline, so the 1st flight/3rd phase (i.e., from mini trampoline take-off to the initial contact with vaulting table) will be a lower parabola with a minimal loss of velocity and greater energy and velocity [ 37 ]. This optimal body position is conditioned by the approach run characteristics as velocity [ 38 , 39 ], individual characteristics, namely, height [ 40 ], strength [ 40 ], power, flexibility, biological development, visual perception and strategy [ 4 , 15 , 41 ] and other constraints, which in practice may reveal a larger variability and adjustment of movement, consequently resulting in the higher number of clusters observed. Figure 5 demonstrates that four clusters (two, three, four and six) with different movement prototypes for phase one have very good average scores (≥9.000 points), reinforcing the acceptance of an optimal and needed movement variability, without considerably reducing score.…”
Section: Discussionmentioning
confidence: 99%
“…During this phase gymnasts start to approach an optimal body position to contact the mini trampoline, so the 1st flight/3rd phase (i.e., from mini trampoline take-off to the initial contact with vaulting table) will be a lower parabola with a minimal loss of velocity and greater energy and velocity [ 37 ]. This optimal body position is conditioned by the approach run characteristics as velocity [ 38 , 39 ], individual characteristics, namely, height [ 40 ], strength [ 40 ], power, flexibility, biological development, visual perception and strategy [ 4 , 15 , 41 ] and other constraints, which in practice may reveal a larger variability and adjustment of movement, consequently resulting in the higher number of clusters observed. Figure 5 demonstrates that four clusters (two, three, four and six) with different movement prototypes for phase one have very good average scores (≥9.000 points), reinforcing the acceptance of an optimal and needed movement variability, without considerably reducing score.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the number and duration of fixations (Aziz, 2017) and their locations (Barreto et al, 2021) are task and context specific. Despite this, 69% of eye tracking studies have been conducted in laboratory conditions (Abernethy et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Behavior can be characterized by variables such as the duration and number of fixations. Studies have demonstrated that gaze behaviors differ according to the study conditions, for example in representative task designs vs. well-controlled laboratory experiments (Barreto et al, 2021), and that behavior must be evaluated in real settings involving a variety of situations (Brenner and Smeets, 2017) which are ecologically valid (Casanova et al, 2013). Furthermore, gaze behavior can only be fully understood if it is related to performance (Chia et al, 2017).…”
Section: Introductionmentioning
confidence: 99%